Evaluating the effect of nitrogen fertilizer rate and source on the performance of open‐pollinated rye (Secale cereale L.) cultivars in contrasting European environments. Issue 2 (16th February 2022) - Tupits, Ilme; Tamm, Ilmar; Magistrali, Amelia; Rempelos, Leonidas; Cakmak, Ismail; Leifert, Carlo; Grausgruber, Heinrich; Wilkinson, Andrew; Butler, Gillian; Bilsborrow, Paul
Abstract: Rye ( Secale cereale L.) is a minor cereal with potential to support sustainable farming practices. This study evaluated the performance of four old and modern European open‐pollinated winter rye cultivars grown with different nitrogen (N) sources (cattle slurry, farmyard manure, biogas digestate, mineral N) at two rates of N 50 and 100 kg ha −1 in the United Kingdom and Estonia, in the 2014–2015 and 2015–2016 growing seasons. Grain yield in Estonia was higher than the United Kingdom (6.2 vs. 4.8 t ha −1 ), which was attributed to a higher ear density (409.4 vs. 249.7 ears m −2 ) and grain number per ear (50.2 vs. 43.2), although 1, 000‐grain weight was higher in the United Kingdom. There were clear differences between sites in the response to N source with significant N source × year interactions. Biogas digestate and mineral N produced higher grain yield than farmyard manure and cattle slurry in the United Kingdom, whereas in Estonia cattle slurry had a lower grain yield than the other N sources. Foliar diseases were absent in Estonia and in the United Kingdom, and N source only affected powdery mildew and leaf blotch on Leaf 2. The response of grain quality to N source and variety was consistent across both sites. The modern variety Elias had the highest Hagberg falling number and specific weight but the lowest protein content, whereas the variety Schlägler had the highest protein content but lowest specific weight. The benefits of selecting cultivars for specific environments are shown by the interactions between genotype and environment. Core Ideas: The study evaluates the response of four different rye cultivars to rate and type of fertilizer. Biogas digestate showed value as a N fertilizer producing a yield similar to mineral N. High grain yields in Estonia were associated with higher ear number and grains per ear. Clear genotype × environment interactions can help target cultivars to suited environments. With low disease levels rye provides an opportunity for organic and low‐input growers.